CLASSROOM READING HELPED PROGRAMS FOR COMIC MEDIA TO IMPROVE THE INTEREST OF READING BASIC SCHOOL STUDENTS - Rohmah Suciningrum (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Reading is an important activity that is used as a habituation activity for students in elementary school. Classroom Reading Program is a systematic and structured classroom reading program. Comics is one medium that can be used to increase interest in reading learners. Classroom Reading The comic media assisted program is expected to increase students' reading interest in elementary schools. This research method is descriptive qualitative. Research data related to students' interest in reading through the application of classroom reading assisted program comic media collected through questionnaire instruments, then the results of questionnaires were analyzed based on Linkert guidelines. In addition to questionnaires, the techniques used to retrieve data are interviews, observation and documentation studies. The aim of the study was to find out how the application of Classroom Reading was a comic media assisted program in increasing students' reading interest. After the Classroom Reading the comic media assisted program was implemented, it was proven that students' interest in reading increased. The average increase in the interest of learners by 90%.